Training Program for Presarcopenic Elderly Patients - Mangold, Roland; Márton, Lilla; Lajkó, Patrícia; Gadó, Klára (Magyar Gerontológia, 2025)
Purpose: Our aim was to test a training program designed to decrease/reverse the deleterious effects of sarcopenia: a generalized and progressive loss of muscle mass and muscle strength and function. Materials and methods: An intervention group of 9 participants and a control group of 7 participants took part in the pilot study, aged 65+, and former patients of the Szent Rókus Hospital. We measured grip strength, functional capacity with the Timed Up and Go test, and the presence and severity of sarcopenia with the SARC-F questionnaire. A two-month training period followed, with biweekly workouts. After which we reassessed and used a paired samples T-Test in JASP 0.16.4.0.. A focus group interview was used to collect participants’ thoughts and feelings regarding the training period. Results: The intervention group showed a positive, nonsignificant change in their SARC-F scores (p=0.080). Their functional capacity improved significantly (p=0.033). Their muscle strength also improved significantly (p=0.006). The control group’s SARC-F scores decreased, (p=0.423), performed the TUG test slower (p=0.114) and their grip strength decreased (p=0.477). We received unanimously positive answers at the focus group interview. Conclusion: The exercise program improved the functional capacity and muscle strength of the participants; thus, it would be worthwhile for physiotherapists working with older people to familiarize themselves with principles used here and to utilize a similar program.